CD44 as a cancer stem cell marker and its prognostic value in patients with ovarian carcinoma. (2nd January 2018) - Bartakova, Alena; Michalova, Kveta; Presl, Jiri; Vlasak, Pavel; Kostun, Jan; Bouda, Jiri
Abstract: The aim of our study was to clarify whether the CD44 adhesion molecule as a cancer stem cell marker could also serve as a prognostic factor in patients with epithelial ovarian cancer (EOC). A retrospective study was performed on 87 patients with histologically verified EOC. Specimens of both primary tumour and implantation metastases were tested from 48 of them. CD44 expression was detected by immunohistochemistry. We looked for the cut-off levels of CD44 expression using the Cox regression model. We confirmed statistically significant prognostic factors for overall survival (OS) and disease-free interval (DFI) to be: stage of the disease, postoperative residual tumour and papillary serous histological type. We demonstrated a statistically significant correlation between low CD44 expression and serous papillary carcinoma histotype, tumour recurrence and chemoresistance at a value below 2%. CD44 was neither a prognostic factor of OS nor of DFI. IMPACT STATEMENT: What is already known about this subject: Epithelial ovarian cancer is the second most common gynaecological cancer in developed countries. Despite great efforts devoted to ovarian cancer research during past decades, levels of patient mortality have changed very little. Cancer stem cells (CSCs) are subpopulations of cells with typical characteristics of stem cells – i.e. the ability to self-renew and differentiate in a variety of cell types. The main surface marker typical for CSCs is CD44. The aim of our study was to clarify whether the CD44 as a CSCs marker could serve as a prognostic factor in patients with epithelial ovarian cancer. Previous studies published on this topic revealed controversial results. The novelty of our study lies in looking for the cut-off using the Cox regression model. What this study adds: We demonstrated a statistically significant correlation between low CD44 expression and serous papillary carcinoma histotype, tumour recurrence and chemoresistance at a value below 2%, however, CD44 was neither a prognostic factor of overall survival nor of disease-free interval. We propose to investigate other markers including other CSCs as a prognostic factors or potential aims for targeted therapy in ovarian cancer.